2021
DOI: 10.1093/cercor/bhab391
|View full text |Cite
|
Sign up to set email alerts
|

Striatal BOLD and midfrontal theta power express motivation for action

Abstract: Action selection is biased by the valence of anticipated outcomes. To assess mechanisms by which these motivational biases are expressed and controlled, we measured simultaneous EEG-fMRI during a motivational Go/NoGo learning task (N = 36), leveraging the temporal resolution of EEG and subcortical access of fMRI. VmPFC BOLD encoded cue valence, importantly predicting trial-by-trial valence-driven response speed differences and EEG theta power around cue onset. In contrast, striatal BOLD encoded selection of ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 99 publications
8
39
0
Order By: Relevance
“…Such a relationship has been reported in previous simultaneous EEG-fMRI studies. Specifically, MFT amplitude showed negative correlations to BOLD signal in the default mode network, including the midline prefrontal cortex, during the resting state (Prestel et al, 2018; Scheeringa et al, 2008), working memory (Scheeringa et al, 2009), and decision (Algermissen et al, 2021) tasks. Scheeringa and colleagues (2009) suggested that theta serves a role in task-orientedness by inhibiting irrelevant information and enabling optimal performance on a task.…”
Section: Discussionmentioning
confidence: 99%
“…Such a relationship has been reported in previous simultaneous EEG-fMRI studies. Specifically, MFT amplitude showed negative correlations to BOLD signal in the default mode network, including the midline prefrontal cortex, during the resting state (Prestel et al, 2018; Scheeringa et al, 2008), working memory (Scheeringa et al, 2009), and decision (Algermissen et al, 2021) tasks. Scheeringa and colleagues (2009) suggested that theta serves a role in task-orientedness by inhibiting irrelevant information and enabling optimal performance on a task.…”
Section: Discussionmentioning
confidence: 99%
“…These brain regions belong to a wider network, often referred to as the salience network, which is sensitive to homeostatically relevant stimuli independent of whether their valence is negative (penalising) or positive (reinforcing) 18 . It is becoming increasingly clear that neural responses in the absolute PE network rise quickly after an outcome is revealed [24][25][26] . Here we observe that the CRS is parametrically modulated by the outcome's absolute PE and that this is mainly due to the first heartbeat recorded immediately after the outcome onset.…”
Section: Discussionmentioning
confidence: 99%
“…The topographical distribution of the neural phenomena comprising the HEP was defined by computing mean voltages of the HEP time-locked to R-wave onset for all trials at the group level using the cluster-based permutation test including all electrodes sites and across the entire time window where the HEP typically takes place, this is, 0.1-0.5s 22 2, 24 25 . In this analysis, no a-priori electrode clusters were formed (all active electrodes were treated as a distinct variable).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like outcome anticipation, intertemporal decisionmaking usually includes an evaluation process and instrumental approach behavior (see also Scheres et al (2013)). Therefore, differences in neural activation between loss and reward decisionmaking could be confounded with differences in the motivational value of the reward or loss as reflected in the activation during reward and loss anticipation (Algermissen et al, 2021). To this end, we developed a sequence of decision-making and outcome anticipation by combining intertemporal choice tasks with a MID task (Kirsch et al, 2003).This further allowed us to conduct a MID task with highly salient outcomes which have been chosen by the participants themselves.…”
Section: Introductionmentioning
confidence: 99%